Efektifitas Pelaksanaan Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Kecamatan Sukamara Kabupaten Sukamara - Riduan Riduan; Muhamad Yusuf; Putri Irianti Sintaman (Pencerah Publik, 2020)
The purpose of this research is to know the effectiveness of the implementation of the complete systematic land registration Program (PTSL) in Sukamara district of Sukamara District and the effective inhibiting factors of its implementation. The study used a qualitative approach. The research Data is derived from live observations, interviews, and collecting documents. The informant in this research is the land of the province of central Kalimantan, the National Land Agency (BPN) Sukamara, Department of Population and Civil registration of Kapubaten Sukamara, District Sukamara, Government village and society/landowners. The results showed that the implementation of the program was quite effective with the addition of personnel and administrative force in the success of the program. This is also because the flow and stage of implementation of the program is already running according to the existing rules although in the process there are some constraints. Although the target is still not reached in each year but there is an increase in access in the next year. The inhibitory factors in the of are still found in the field of unknown land ownership, there are still many landowners who are not present at the time of measurement, low public awareness/landowners in clearing and making a barrier to the land, the low awareness of public to follow the program PTSL, still found population data that is not synced with land mail and the presence of land that is requested not have sppt-un land running.